2014
DOI: 10.1039/c4cp01093k
|View full text |Cite
|
Sign up to set email alerts
|

Dipole-induced conductivity enhancement by n-type inclusion in a p-type system: α-Fe2O3–PEDOT:PSS nanocomposites

Abstract: Hematite (α-Fe2O3) nanoparticles of two different shapes but of same size (ca. 40 nm) were dispersed in PEDOT:PSS matrices in various concentration ranges (0-7 wt%) to study the consequent changes in conductivity in the dark and under solar illumination conditions. Within a distinct range of concentration, a distinct increase in the conductivity was observed for both spherical and cubical particle population. We ascribed this effect to the generalized Poole-Frenkel theory of conduction in conjunction with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…After plasma treatment the pH of the solution increased slightly to 4.7. Depending on IS, this is within the pH range where electrostatic stabilisation is less effective, and in other reports, pH values around 2 were typically required for NP stabilisation in PEDOT:PSS 31 32 33 34 . The plasma treatment has clearly shown the ability to improve the dispersion of the NPs.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…After plasma treatment the pH of the solution increased slightly to 4.7. Depending on IS, this is within the pH range where electrostatic stabilisation is less effective, and in other reports, pH values around 2 were typically required for NP stabilisation in PEDOT:PSS 31 32 33 34 . The plasma treatment has clearly shown the ability to improve the dispersion of the NPs.…”
Section: Discussionmentioning
confidence: 76%
“…which was attributed to the insulating nature of the particles. However Raccis et al 32 observed that, within a very narrow range of concentrations (~1.2%), the conductivity of PEDOT-PSS could be increased up to eight-fold after NP inclusion. Understanding PEDOT:PSS conduction mechanisms is a significant challenge in the search for enhanced or selectable conductivity and resistance to degradation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, it is evident from the literature that the embedment of particles of size between 20 and 50 nm is optimum for better effect on the properties of the organic layer. Since the thickness of the organic layer is limited, larger particle sizes deteriorate the layer, while smaller particle sizes are more difficult to synthesize 35,36,39,40 …”
Section: Introductionmentioning
confidence: 99%